Italian Association of Sleep Medicine (AIMS) position statement and guideline on the treatment of menopausal sleep disorders. (November 2019) - Silvestri, R.; Aricò, I.; Bonanni, E.; Bonsignore, M.; Caretto, M.; Caruso, D.; Di Perri, M.C.; Galletta, S.; Lecca, R.M.; Lombardi, C.; Maestri, M.; Miccoli, M.; et al.
Highlights: Vasomotor symptoms in postmenopausal women correlate with insomnia and depression. Postmenopausal insomnia is best managed with menopausal hormone therapy and cognitive behavioral therapy. Selective serotonin (SSRIs) and dual (SNRIs) reuptake inhibitors are also indicated for postmenopausal insomnia with vasomotor symptoms. Continuous positive airway pressure and mandibular advancement devices improve cardiovascular outcome in postmenopausal women. Abstract: Insomnia, vasomotor symptoms (VMS) and depression often co-occur after the menopause, with consequent health problems and reductions in quality of life. The aim of this position statement is to provide evidence-based advice on the management of postmenopausal sleep disorders derived from a systematic review of the literature. The latter yielded results on VMS, insomnia, circadian rhythm disorders, obstructive sleep apnea (OSA) and restless leg syndrome (RLS). Overall, the studies show that menopausal hormone therapy (MHT) improves VMS, insomnia, and mood. Several antidepressants can improve insomnia, either on their own or in association with MHT; these include selective serotonin reuptake inhibitors (SSRIs), serotonin and norepinephrine reuptake inhibitors (SNRIs), and mirtazapine. Long-term benefits for postmenopausal insomnia may also be achieved with non-drug strategies such as cognitive behavioral therapy (CBT) and aerobic exercise. Continuous positive airway pressure (CPAP) and mandibular advancement devices (MADs) both reduce blood pressure and cortisol levels in postmenopausal women suffering from OSA. However, the data regarding MHT on postmenopausal restless legs syndrome are conflicting.